2018
DOI: 10.1002/da.22790
|View full text |Cite
|
Sign up to set email alerts
|

The association between anxiety, traumatic stress, and obsessive-compulsive disorders and chronic inflammation: A systematic review and meta-analysis

Abstract: These data demonstrate the association between inflammatory dysregulation and diagnoses associated with chronic, impactful, and severe anxiety and provides insight into the way that anxiety, and in particular PTSD, is related to certain inflammatory markers. In doing so, these findings may provide an initial step in disentangling the relationship between anxiety and basic health processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 89 publications
5
105
1
2
Order By: Relevance
“…In finding that peripheral inflammation in RSDS was most tightly- linked with the EZM—a test of anxiety-like behavior—it is worth noting the DSM-IV originally characterized PTSD under the umbrella of anxiety disorders ( American Psychiatric Association, 2000 ). There is a breadth of clinical literature demonstrating differences in peripheral inflammation in patients with PTSD as well as other anxiety disorders ( O’Donovan, 2015 ; Neigh and Ali, 2016 ; Boscarino, 2004 ; Kim et al, 2020 ; Renna et al, 2018 ). Importantly, many of the cytokines we found to be differentially elevated in control versus RSDS have also been shown to be elevated in human plasma from patients with PTSD, such as IL-2, IL-6, IL-17, and TNFα (summarized well by Wang et al ) ( Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In finding that peripheral inflammation in RSDS was most tightly- linked with the EZM—a test of anxiety-like behavior—it is worth noting the DSM-IV originally characterized PTSD under the umbrella of anxiety disorders ( American Psychiatric Association, 2000 ). There is a breadth of clinical literature demonstrating differences in peripheral inflammation in patients with PTSD as well as other anxiety disorders ( O’Donovan, 2015 ; Neigh and Ali, 2016 ; Boscarino, 2004 ; Kim et al, 2020 ; Renna et al, 2018 ). Importantly, many of the cytokines we found to be differentially elevated in control versus RSDS have also been shown to be elevated in human plasma from patients with PTSD, such as IL-2, IL-6, IL-17, and TNFα (summarized well by Wang et al ) ( Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… 46 Mindfulness-based interventions, understood as an awareness of the experience of the present moment and emphasizing the attention paid to one’s thoughts, bodily sensations and emotions, have shown to be effective among patients with IBD. 47 They often combine meditation with contemporary cognitive–behavioral approaches, and several mechanisms behind their effectiveness have been identified. 48 In fact, their positive effects on various mental health conditions have been reported in diverse clinical and non-clinical populations.…”
Section: The Decaloguementioning
confidence: 99%
“…Sickness behavior symptoms show a considerable overlap with depressive symptoms like anhedonia, anorexia, low concentration, low energy, low libido, psychomotor slowness, irritability; and researchers have hypothesized that depression is a maladaptive or exacerbated form of sickness behavior in some patients with chronic low-grade inflammation 15 20 . Besides their reward-sensitivity related symptoms, recent studies suggest that also trauma- and anxiety-related symptoms are related to inflammatory markers, resulting in a mix of overlapping symptoms of mood, anxiety, and post-traumatic stress disorder 13 , 21 23 . A causal pathway in which inflammation causes symptoms of anxiety is less established as studies show that inflammatory levels increase when study participants became anxious 24 , 25 , and a large longitudinal study found that anxiety predicted inflammation in the future but not vice versa 26 .…”
Section: Introductionmentioning
confidence: 99%